Guilds of Aculeata (Hymenoptera) visiting the goldenrod inflorescences (Solidago L.) in open-field area in «Narochansky» National park - Sheiko, Anna A.; Koroteeva, Daria O.; Buga, Sergey V. (Journal of the Belarusian State University. Ecology, 2022)
The study of anthophilous insects carried out in 2019-2021 in open field areas in the territory of Narochansky National Park revealed 42 species for the flower visitor guild of native European goldenrod (Solidago virgaurea L.) and for the flower-visitor guild of invasive goldenrods Solidago canadensis s. l. - 50 species of Aculeata (Hymenoptera). The taxonomic structure of guilds is different: only 11 species are present in both guilds, among visitors of S. virgaurea inflorescences the species richness of Apoidea is higher (38 species, 90 % of their total number), whereas for S. canadensis inflorescences -of Vespoidea s. l. (31 species, 62 %). There were no dominant species in the studied guilds; in the guild of S. virgaurea inflorescence visitors, the group of common species included bumblebees Bombus lucorum L. and Bombus (Psithyrus) bohemicus Seidl, the group of numerous species - bumblebees Bombus humilis Ill., Bombus lapidarius L., Bombus pratorum L., Bombus terrestris L. and Cuckoo bumblebee Bombus (Psithyrus) rupestris F. Polistine wasps Polistes nimpha Christ and Polistes dominula Christ were common among visitors of S. canadensis inflorescences; Ancistrocerus trifasciatus Mull., Philanthus triangulum F., Lasioglossum varipes Morawitz, and B. terrestris were numerous. The relative abundance of B. terrestris was the highest, approaching the threshold value for assignment to the group of numerous species. It is suggested that high relative abundance of Vespoidea s. l. visiting inflorescences of invasive goldenrods is connected to the fact that adult wasps not only feed on flowers, but prey on small insects that are numerous here.
Keywords: Belarusian Lakeland; biological invasions; pollinators; Solidago canadensis s. l.; Solidago virgaurea; alien species